KRITIK IBNU TAIMIYAH TERHADAP TASAWUF ANTARA PURIFIKASI DAN PENOLAKAN - Nadia Amanda (Yayasan An-Nur Meunara Baro, 2025)
Sufism has long been an integral part of Islamic intellectual and spiritual tradition, offering a path of inner purification and ethical refinement. However, throughout its historical development, Sufism has also faced critical scrutiny, especially from scholars who prioritize theological purity and strict adherence to Sharia. Among these critics, Ibn Taymiyyah stands out as a central figure who rigorously challenged various aspects of Sufism, particularly those rooted in philosophical mysticism. His criticism, however, does not represent a wholesale rejection of Sufism, but rather a call for purifying Islamic teachings from elements of bid‘ah (religious innovation), syncretism, and speculative metaphysics that deviate from core Islamic tenets. Ibn Taymiyyah draws a clear distinction between Sunni Sufism, which emphasizes piety and ethical conduct, and philosophical Sufism, which promotes mystical doctrines such as wahdat al-wujūd (unity of being), hulūl (incarnation), and ittihād (union with the divine). This article aims to explore Ibn Taymiyyah’s critical stance using historical and theological approaches, and to assess the relevance of his views in the context of contemporary Islamic discourse. This study adopts a library research method and descriptive-critical analysis of both primary sources and recent academic literature from 2018–2025. The findings indicate that Ibn Taymiyyah’s approach is more corrective than dismissive, as he still acknowledges the authenticity of Sufi figures such as Al-Junaid and Al-Fudhail ibn ‘Iyadh, who adhered strictly to Islamic law in their spiritual practices. His perspective offers a methodological foundation for maintaining balance between sound creed and legitimate spirituality in the modern era.